Case report: serum cardiac troponin I concentration in three calves with doxycycline overdose - Karapinar, T.; Tumer, K. C.; Caliskan, M.; Yilmaz, O. (Ecole Nationale Veterinaire Toulouse, 2019)
Doxycycline is used to treat or to prevent respiratory infections in calves. Doxycycline can be easily administered to calves in milk or milk replacers; under farm conditions, therefore, overdose may occur in calves. A male, one-month-old Simmental calf was brought to Firat University Veterinary Animal Teaching Hospital because he had anorexia and lethargy. Clinical examination revealed a swollen tongue and tongue paralysis. Doxycycline hyclate, total amount 1500 mg (which is 6.5 times the recommended dose of 5 mg/kg BW), had been administered orally to the calf 3 days previously to treat diarrhea. Based on the history and the results of clinical examination the calf was diagnosed with doxycycline overdose. The case history revealed that two calves on the same farm were also suffering from doxycycline overdose and another calf had died suddenly after doxycycline administration. Increased serum cardiac troponin I (cTnI) concentration of the three calves was determined with a human commercial cTnI assay. The first calf progressively deteriorated and died on day 9 despite decreasing serum cTnI concentration. The serum cTnI concentration of the other two calves returned to physiological levels. In this report, calves with doxycycline overdose had increased serum concentrations of cTnI. Further studies are required to detect whether temporary myocardial damage occurs in doxycycline-overdosed calves.
Keywords: Antibiotic; calf; doxycycline; myocarditis; troponin